In vivo biochemical changes occurring at different time intervals in white spot syndrome virus infected shrimp, treated with anti-WSSV drug derived from marine plants - Somnath Chakraborty and Upasana Ghosh (Journal of Applied Pharmaceutical Science, 2013)
White spot syndrome virus (WSSV), is the most contagious pathogen of cultured shrimp that causes mass mortality, leading to huge economic loss to the shrimp industry. The lack of effective therapeutic or prophylactic measures has aggravated the situation, necessitating the development of antiviral drugs. With this objective, the antiviral activity of the drug, (MP07X -derived from the marine plant) in the host, Litopenaeus vannamei was evaluated. The biochemical changes aggravated by WSSV in the host, and the in vivo efficacy of the drug in the host -pathogen interaction were analyzed. The survival percentage of the treated (with MP07X) WSSV infected host was 85 %. Significant results were obtained from the cytotoxicity assays of the drug in both the brine shrimp and host. A total of 9 biochemical parameters such as, total protein, total carbohydrate, total glucose, total free amino acid, total fatty acid, fructose 1, 6 diphosphatase, aldolase, glucose 6 phosphatase and glucose 6 phosphate dehydrogenase were examined for healthy (NEG), WSSV infected (POS) and test sample (TS) shrimps. Significant differences (p < 0.01) were observed between the POS, NEG and TS in the biochemical variables at different time intervals post infection with WSSV. In the case of POS, significantly (p < 0.01) reduced variables were observed when compared to the NEG. In contrast, significant (p < 0.01) elevations were observed in the TS after a certain time interval due to the anti-WSSV activity of MP07X. Neither the VP 28 gene nor the immediate early genes (ie 1) were expressed in the host at the 42nd and 84th hrs. Thus, in accordance with the above results it can be concluded that acute WSSV infection triggers alterations in biochemical parameters in L. vannamei and at the same time the drug is efficient enough to combat the deadly virus and can increase the survivability of the host.
Keywords: Litopenaeus vannamei, anti – WSSV drug, biochemical parameters, viral gene, immune gene.